2017
DOI: 10.1177/0093854817719482
|View full text |Cite
|
Sign up to set email alerts
|

Broken Legs, Clinical Overrides, and Recidivism Risk: An Analysis of Decisions to Adjust Risk Levels With the LS/CMI

Abstract: Risk assessment practices have evolved considerably over the past three decades. Structured assessments of recidivism risk allow for the proper identification of criminogenic needs, which in turn, allow decision makers to make informed recommendations regarding criminal justice interventions and measures. Although actuarial assessments are common practice, situations exist where evaluators may call into doubt the risk assessment’s conclusions, and may exercise their discretionary professional judgment to adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
52
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 40 publications
13
52
3
Order By: Relevance
“…It could also be possible that some jurisdictions carry a more retributive philosophy and use overrides with sex offenders as a means of exacting sanctions that require increased supervision and treatment . Second, it is important to examine the influence of overrides on the predictive validity of risk assessment because researchers have found that predictive validity of a tool is usually harmed when overrides are used to adjust the risk score or level of a risk assessment (Guay & Parent, ; Wormith et al., ). Overrides may be especially harmful for predictive validity when examining sex offenders because of their high rate of use with this group (Carns & Martin, ; Wormith et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also be possible that some jurisdictions carry a more retributive philosophy and use overrides with sex offenders as a means of exacting sanctions that require increased supervision and treatment . Second, it is important to examine the influence of overrides on the predictive validity of risk assessment because researchers have found that predictive validity of a tool is usually harmed when overrides are used to adjust the risk score or level of a risk assessment (Guay & Parent, ; Wormith et al., ). Overrides may be especially harmful for predictive validity when examining sex offenders because of their high rate of use with this group (Carns & Martin, ; Wormith et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, a scant amount of research on overrides has been conducted with youth risk assessment. In fact, in the studies that were reviewed by Guay and Parent () and Wormith and colleagues (), the researchers used adult samples. They were reviewed here, though, to give a sense of what has been found in past research and to show the paucity of research that exists with youth samples.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the predictive validity of overrides is limited and the findings that do exist are mixed. 49,50 Some risk assessment tools are designed to predict general recidivism risk, including committing a new crime (nonviolent and violent) and violating conditions of probation or parole. More than 60 such risk assessment tools have been identified as being used in criminal justice settings in the United States.…”
Section: Predicting Outcomesmentioning
confidence: 99%
“…It further provides a common language for professionals to use when discussing risk and risk mitigation (Canales et al, 2013). More importantly, when professionals deviate from the risk appraisal generated by evidence-based risk assessment instruments, the judgments rendered tend to be less accurate in their capacity to predict future criminal behaviour (Chappell et al, 2013;Guay & Parent, 2018;Wormith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%